THE INFLUENCE OF PRICE AND PRODUCT QUALITY ON CUSTOMER SATISFACTION WITH PURCHASE DECISION AS MEDIATION VARIABLE IN SOMETHINC SERUM SKINCARE PRODUCTS IN INDONESIA - Azyyati Muthmainnah; Heriyadi Heriyadi; Wenny Pebrianti; Ramadania Ramadania; Syahbandi Syahbandi (Jurnal Ekonomi, 2023)
This research aims to determine and evaluate the direct influence of product quality and price on customer satisfaction and the indirect effect of purchasing decisions as an intervening variable on customer satisfaction. The population of this study consisted of individuals domiciled in Indonesia who had bought and used Somethinc serum skin care products. A total of 203 respondents met the research requirements, including being Indonesian citizens, having purchased and used Somethinc serum skin care products, and being at least 17 years old. On several islands in Indonesia, an online questionnaire was used as a data collection technique. This research uses a purposive sampling strategy. A strategy known as causal design was used to test the hypotheses developed in this research. The AMOS 24 tool is used in Structural Equation Modeling (SEM) testing to determine the relationship between independent and dependent variables. Research findings show that price significantly influences purchasing decisions, as does product quality. Price also has a significant influence on customer satisfaction. Product quality has a considerable impact on customer satisfaction. Purchasing decisions also have a substantial effect on customer satisfaction. However, price does not significantly affect consumer satisfaction through purchasing decisions as an intervening variable. On the other hand, product quality significantly influences customer satisfaction through purchasing decisions as an intervening variable.